The Ramadan effect: Illusion or reality? - Azwar Ramadhana Sonjaya; Imam Wahyudi (Arab Economic and Business Journal, 2016)
Empirical tests of the efficient market hypothesis (EMH) have been repeated by many researchers with varying results, with several supporting it and others finding no clear evidence for it. One of the results that weakens the EMH is the study of such anomalies as the Ramadan effect. Anomaly studies are also denied by recent studies that demonstrated proof of the weakening and even disappearance of anomalous effects. This research tests the persistence of the Ramadan effect in the stock returns in 10 Muslim-majority countries. We have found that the Ramadan effect is present, but it is not persistent. This finding is consistent with the finding from the test of efficient market form, which indicated that the markets of all 10 Muslim-majority countries are not efficient. When economic crisis is considered as an influencing factor, the Ramadan effect is still not persistently present.
Keywords: D84; E44; G02; G14; 330; Efficient market; Ramadan effect; Anomaly; Abnormal return; Crisis